1980
DOI: 10.1007/bf01869457
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport across the isolated intestinal mucosa of the winter flounder,Pseudopleuronectes americanus: II. Effects of cyclic AMP

Abstract: Addition of cyclic AMP and theophylline to the intestinal mucosa of the winter flounder, Pseudopleuronectes americanus decreased short-circuit current and net Na and Cl absorption and increased total conductance and the serosa-to-mucosa unidirectional Cl flux (JsmCl). The last two changes were independent of the original rate of NaCl absorption and persisted even when net absorption of Na and Cl had been abolished by ouabain. Voltage clamp experiments revealed that the increment in JsmCl produced by cyclic AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…It is, therefore, possible that the reduction of villus height and other morphological changes are a direct consequence of N2M affecting crypt cell mitoses. This would affect normal epithelial cell replacement and hence height of villi, and also crypt functions which by general consensus (Roggin et al, 1972;Field et-al., 1980;Welsh et al, 1982) are involved in normal secretion. Increased rates of villus base/crypt cell division are involved in the hypersecretory phase of rotavirus diarrhoea (Collins et al, 1988;Spencer et al, in press) and have been implicated in other bacterial toxin-induced diarrhoeas (Stephen and Osborne, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, possible that the reduction of villus height and other morphological changes are a direct consequence of N2M affecting crypt cell mitoses. This would affect normal epithelial cell replacement and hence height of villi, and also crypt functions which by general consensus (Roggin et al, 1972;Field et-al., 1980;Welsh et al, 1982) are involved in normal secretion. Increased rates of villus base/crypt cell division are involved in the hypersecretory phase of rotavirus diarrhoea (Collins et al, 1988;Spencer et al, in press) and have been implicated in other bacterial toxin-induced diarrhoeas (Stephen and Osborne, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The inward-directed electrochemical Na + gradient facilitates Na + uptake across the apical membrane, which is generally ascribed to two parallel co-transport systems: the absorptive Na + :K + :2Cl -cotransporter (NKCC2 in the following) and the Na + :Cl -cotransporter (NC in the following) (Field et al, 1980;Frizzell et al, 1979;Halm et al, 1985;Musch et al, 1982;Cutler and Cramb, 2002). The coupling of Na + uptake to the uptake of K + and Cl -is not necessary for Na + from a thermodynamical perspective because the electrochemical gradient for Na + is inwardly directed.…”
Section: Na + Absorption By the Marine Teleost Intestinementioning
confidence: 99%
“…Reducing the saline's [HCO 3 Ϫ ] from 20 mM to 5 mM induces an ϳ60% reduction of Cl Ϫ absorption and I sc , a 30% reduction of Na ϩ absorption, and a significant increase in G te (12,13). HCO 3 Ϫ stimulation of ion absorption has been attributed to increases in pH (12), which stimulates NaCl and water absorption on its own (44).…”
mentioning
confidence: 96%
“…Some studies have applied 8-Br-cAMP in combination with theophylline, and they have found robust inhibition of I sc and Na ϩ and Cl Ϫ absorption (13,15). However, theophylline is a nonspecific phosphodiesterase inhibitor that prevents both cAMP and cGMP degradation.…”
mentioning
confidence: 98%